PENGARUH KUALITAS PELAYANAN, FASILITAS, DAN IKLAN DIGITAL TERHADAP TINGKAT HUNIAN REDDOORZ PLUS NEAR KEPRI MALL - Tan, Frances; Syaiful, Syaifullah (LPPM Universitas Putera Batam, 2021)
The business scope, especially in the service sector, is now growing rapidly, a business that is growing rapidly in Indonesia is tourism. This research aim are: (1) to determine the impact of service quality on occupancy rates; (2) to determine the impact of the facilities on the occupancy rate; (3) to determine the impact of digital advertising on occupancy rates; (4)to determine the impact of service quality, facilities, and digital advertisements on the occupancy rate. This research design used in this research is descriptive research through a quantitative approach. The population in this study were guests of RedDoorz Plus near Kepri Mall. The samples used is 150 respondents with the sampling technique using probability sampling through method simple random sampling. The software used to analyze these data is SPSS version 25. The results of T test explain that service quality and digital advertising partially have significant effect to occupancy rate, but facilities has no significant effect to occupancy rate. From the F test result explain service quality, facilities, and digital advertising together have significant effect on the occupancy rate.